2010
DOI: 10.1093/cvr/cvq358
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of ectopic trypsins in the myocardium by influenza A virus infection triggers acute myocarditis

Abstract: AimsInfluenza A virus (IAV) infection markedly up-regulates ectopic trypsins in various organs, viral envelope glycoprotein processing proteases, which are pre-requisites for virus entry and multiplication. We investigated the pathological roles of trypsin up-regulation in the progression of IAV-induced myocarditis, cytokine induction, and viral replication in the hearts, and also investigated the protective effects of trypsin inhibitor on cardiac dysfunction in vivo and selective knockdown of trypsin on IAV-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(77 citation statements)
references
References 37 publications
(55 reference statements)
3
74
0
Order By: Relevance
“…However, this effect is likely due to the direct suppression of viral replication by IFN-␥ or IFN-␥-mediated activation of natural killer cells (46). Acute MAV-1 infection caused cardiac dysfunction in neonatal mice, similar to decreased cardiac function seen after infection with influenza A virus or CVB3 (30,31). The significantly decreased cardiac function in MAV-1-infected mice that we observed at 10 days p.i.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…However, this effect is likely due to the direct suppression of viral replication by IFN-␥ or IFN-␥-mediated activation of natural killer cells (46). Acute MAV-1 infection caused cardiac dysfunction in neonatal mice, similar to decreased cardiac function seen after infection with influenza A virus or CVB3 (30,31). The significantly decreased cardiac function in MAV-1-infected mice that we observed at 10 days p.i.…”
Section: Discussionsupporting
confidence: 75%
“…Acute viral myocarditis often results in decreased cardiac function (30,31). To determine whether our histological observations correlated with measurements of cardiac function, we assessed heart function by echocardiography.…”
Section: Mav-1 Infects Primary Cardiac Myocytes Ex Vivo and Hearts Inmentioning
confidence: 99%
“…However, we did not analyze myocardial virus titer or neutralizing antibody titers, which is one of the limitations of this study [29][30][31]. Pan et al reported the influenza viral levels in the hearts monitored by the nonstructural protein1 gene and nucleoprotein was in peak on day 6 [32]. However, there is no evidence of viable virus in this paper.…”
Section: Discussionmentioning
confidence: 74%
“…However the number of influenza myocarditis increased in the H1N1 pandemic, and it was serious problem for cardiologists [12,13]. The pathological effects of influenza viral myocarditis in humans and mice are reportedly milder and more localized than those seen in coxsackievirus myocarditis [32][33][34][35]. In this study, histological findings showed localized myocarditis with lymphocyte infiltration, and myocarditis lesions were found in the perivascular area, or myocarditis was associated with pericarditis.…”
Section: Citationmentioning
confidence: 79%
See 1 more Smart Citation